Protective effect of alpha-lipoic acid on bisphenol A-induced learning and memory impairment in developing mice: nNOS and keap1/Nrf2 pathway. (August 2021) - Wu, Dan; Liu, Hezuo; Liu, Yang; Wei, Wei; Sun, Qi; Wen, Deliang; Jia, Lihong
Abstract: The adverse effects of bisphenol A (BPA) on learning and memory may be related with oxidative stress, but the mechanisms are unclear. This study aimed to investigate the mechanism of damaged learning and memory caused by BPA through inducing oxidative stress, as well as to explore whether alpha-lipoic acid (ALA) show a protective action. Female mice were exposed to 0.1 μg/mL BPA, 0.2 μg/mL BPA, 0.6 mg/mL ALA, and 0.2 BPA + ALA through drinking water for 8 weeks. The results showed that ALA protected against the impairment of spatial, recognition, and avoidance memory caused by BPA. ALA replenished the reduce of hippocampus coefficient, serum estradiol (E2) level, and hippocampal neurotransmitters levels induced by BPA. ALA alleviated BPA-induced oxidative stress and hippocampal histological changes. BPA exposure reduced the levels of synaptic structural proteins and PKC/ERK/CREB pathway proteins, and ALA improved these reductions. ALA altered the protein levels of nNOS and keap1/Nrf2 pathway affected by BPA. Our results suggested that impairments of learning and memory caused by BPA was related to the damage of hippocampal synapses mediated by oxidative stress, and ALA protected learning and memory by reducing the oxidative stress induced by BPA through regulating the nNOS and keap1/Nrf2 pathway. Graphical abstract: Image 1 Highlights: Exposure to BPA impaired learning and memory ability by causing synaptic damages. The damages was due to oxidative stress mediated by nNOS and keap1/Nrf2 pathway. ALA alleviated the impairments of BPA by protecting synapses from oxidative damage. The protection of ALA was related to regulation of nNOS and keap1/Nrf2 pathway.